Influence of Celebrity Endorsements on the Purchase of Ice Cream during Covid Pandemic - Saldanha, Avil (Ushus Journal of Business Management, 2022)
Covid 19 had a devastating effect on the Indian ice cream sector, resulting in a huge reduction in ice cream sales. The current study focuses on the possibility of the use of celebrity endorsement by ice cream brands to revive sales. The objectives of the study are to find whether celebrity endorsement influences the frequency of ice cream purchase. The study further investigates the relationship of demographic variables like age, gender, and income on the influence of celebrity endorsement on consumers' purchase intention. 480 respondents of various age groups, genders, and income groups were a part of this study. The respondents were chosen from the South Indian states of Karnataka and Kerala. The results of the study indicate that celebrity endorsement influences the purchase frequency of ice cream by consumers. The study found that perception of celebrity endorsement influence on purchase intention varied among respondents of different gender and income groups respectively. However, no such difference in perception concerning celebrity influence was observed among respondents of various age groups.